Mitigasi Dampak Lingkungan Melalui Biofiltrasi Merkuri (Hg) dari Limbah Tambang Emas Menggunakan Parupuk (Phragmites karka): Pendekatan Fitoremediasi Berbasis Tanaman Lokal dalam Pengolahan Air Limbah Tambang - Ni`mah, Lailan; Suryani, Agus; Anshari, Muhammad Adzhari; Saputra, Hari Apriyan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Mercury pollution from gold mining wastewater remains a major environmental concern due to its persistence and toxicity, driving interest in sustainable, low cost phytoremediation using native wetland plants. This research examines the phytoremediation capacity of Phragmites karka (locally referred to as Parupuk) in mitigating mercury contamination, with a particular focus on mercury (Hg), from wastewater derived from abandoned gold mining sites. A quasi experimental approach was implemented with exposure periods of 0, 3, 6, and 9 days. Approximately 1.5 kg (8 clumps) of live biomass was placed into custom designed 100 L glass bioreactors equipped with continuous water circulation. Key water quality indicators including pH, Chemical Oxygen Demand (COD),Biological Oxygen Demand (BOD), and Hg concentrations were systematically evaluated. Results indicated an increase in pH from 5.8 to 6.0, a 23.17% reduction in BOD (8.9 mg/L), and an 16.67% decline in COD (20 mg/L). The residual Hg concentration reached 0.0044 mg/L, which is below the permissible limit of 0.005 mg/L set by the Indonesian Water Quality Standard (Regulation No. 5/2022). These outcomes demonstrate the dual role of Phragmites karka as both a biological remediator and a fibrous filtration medium for water quality enhancement. Although the system is capable of meeting regulatory thresholds, further research is needed to clarify how Hgsequestration works and to determine the significant and specific contributions to plant structural attributes. This work establishes a scientific basis for further studies aimed at optimizing and scaling phytoremediation technologies for sustainable application in post-mining environments.